Enhancing Decision-Making Efficiency through Contextual Application of Probabilistic Models in Crisis Management - Hordieieva, Inna; Tarasiuk, Halyna; Vasylieva, Nadiia; Kalmykova, Iryna; Paryzkyi, Igor (European Journal of Sustainable Development, 2025)
The current economic crisis makes the research and implementation of new methods of making managerial decisions and managing their alternatives particularly relevant. This article is devoted to a study on applying probability theory to managerial decisions under uncertainty. This study used a general approach that includes diagnostics, synthesis, generalisation, description, induction, deduction and abstraction. The article establishes the rationale for a crisis management strategy. A crisis prevention system is also developed, revising the principles of strategy formation under conditions of uncertainty. Finally, considering the current economic environment, new methods of improving crisis management are proposed. The article presents the results of applying probabilistic models in management decisions that require consideration of the system’s significant internal and external factors. It also emphasises the need to improve the probabilistic management system in economic instability. A model of the mechanism of the anti-frontal system for implementing a crisis management strategy is proposed, which includes undesirable factors along with a block of local unpredictable actions. This methodology aims to increase the potential and practical effectiveness of systematic planning, theoretically facilitating the implementation of erosion strategies, especially in economic supervision. Keywords: probabilistic models, management in crisis conditions, economic feasibility, risk management, strategic development, state regulation, public administration, innovative approaches in public management.